Peningkatan Kapasitas Masyarakat Desa terhadap Pengelolaan Sampah Plastik di Desa Wisata Suak Kecamatan Sidomulyo Kabupaten Lampung Selatan - Apandi Apandi; Dian Kagungan; Simon Sumanjoyo Hutagalung; Dedy Hermawan (Universitas Mathla'ul Anwar Banten, 2021)
INCREASING THE CAPACITY OF VILLAGE COMMUNITIES ON PLASTIC WASTE MANAGEMENT IN THE TOURISM VILLAGE OF SUAK, SIDOMULYO DISTRICT, SOUTH LAMPUNG REGENCY. Based on the situation analysis, the partners identified problems as follows: (1). The problem of plastic waste is still relatively high, so plastic waste management activities are needed to reduce negative impacts, (2). The condition of the community's knowledge capacity as the manager of village tourism in managing plastic waste has not been well identified, (3). The role of village tourism management groups in managing plastic waste is not yet fully optimal. Training and outreach are solutions provided to the target group, in this case the village community group in Suak Village. In the training, knowledge and ways to identify types of plastic waste are provided, select and identify potential plastic waste into various processed products. In practice, several methods are used, namely: (1) lectures, and (2) questions and answers to further improve the training participants' understanding of the material presented. From the activities that have been carried out, the following conclusions are drawn: (1). In the aspect of training implementation achievement, it is known that the training process is in a good category where the target number of training participants is achieved, the training objectives achieved, the material targets that have been planned and the participants' ability to master the material is in the good category, (2). In terms of changes in the knowledge of the imaginary group, it is known that there has been a change in the degree of an average of 20.5%, where the three indicators used have also increased in the range of 15.4% to 23.1%.